The Economic Impact Assessment of the Novel Coronavirus on Tourism and Trade in Kenya: Lessons from Preceding Epidemics - Wanjala, Kevin (Finance & Economics Review, 2020)
Purpose: This paper aims to assess the impact of contemporary Coronavirus Pandemic on tourism and trade with its potential implications on the Kenyan economy. Method: The study considered the cases of Severe Acute Respiratory Syndrome (SARS), Middle East Respiratory Syndrome (MERS) and Ebola epidemics to provide an understanding of the possible impacts that the novel coronavirus pandemic could have on the economy. Results: This study established that the demand and supply shocks of the pandemic will inevitably impact Kenya’s economy specifically, the tourism and trade sectors. The Kenyan government has imposed several measures in an attempt to combat the spread of the coronavirus and cushion the country against a possible economic downturn. The study established that the policies imposed have largely focused on demand shock management. Implications: To effectively minimize the impacts of the pandemic shocks on the economy, it will be prudent for the Kenyan government to design policy responses with a blend of short term and long term orientations. The policies should be multifaceted and their design should involve stakeholders from all the relevant sectors.